2023
DOI: 10.3390/cells12131686
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Stem Cells Isolated from Human Dental Pulp and Exfoliated Deciduous Teeth as Therapeutic Approach in Nervous System Pathologies

Niccolò Candelise,
Francesca Santilli,
Jessica Fabrizi
et al.

Abstract: Despite decades of research, no therapies are available to halt or slow down the course of neuro-degenerative disorders. Most of the drugs developed to fight neurodegeneration are aimed to alleviate symptoms, but none has proven adequate in altering the course of the pathologies. Cell therapy has emerged as an intriguing alternative to the classical pharmacological approach. Cell therapy consists of the transplantation of stem cells that can be obtained from various embryonal and adult tissues. Whereas the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 105 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…TSCI is characterized by the necrosis or apoptosis of neurons and glial cells, demyelination, axon degeneration, and loss of neural circuits, resulting in temporary or permanent loss of motor and sensory abilities, and even paralysis [ 24 ]. Stem cells have shown potential for reconstructing the nervous system due to their ability to proliferate, migrate, and differentiate into neuron-like cells [ 25 27 ]. Previous studies have demonstrated that stem cell transplantation can increase spinal nerve cells and reduce the formation of keratinous scars and cavities in animal models of SCI, which has become a recent focal point in medical research [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…TSCI is characterized by the necrosis or apoptosis of neurons and glial cells, demyelination, axon degeneration, and loss of neural circuits, resulting in temporary or permanent loss of motor and sensory abilities, and even paralysis [ 24 ]. Stem cells have shown potential for reconstructing the nervous system due to their ability to proliferate, migrate, and differentiate into neuron-like cells [ 25 27 ]. Previous studies have demonstrated that stem cell transplantation can increase spinal nerve cells and reduce the formation of keratinous scars and cavities in animal models of SCI, which has become a recent focal point in medical research [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…DPSCs have a high differentiating capacity. In fact, it has been demonstrated that they can differentiate into different cell lineages including endodermal, mesodermal, and ectodermal lineages, respectively [ 19 , 23 , 48 59 ]. Furthermore, with the identification of functional markers and appropriate culture conditions for SC selection, it will be possible to target DPSCs for clinical applications [ 60 ].…”
Section: Maintenance and Survival Of Dscsmentioning
confidence: 99%
“…In 2006, the Mesenchymal and Tissue Stem Cell Committee of the International Society for Cellular Therapy proposed three minimal properties for defining human MSCs: plastic adherence, multilineage differentiation (chondrocytes, osteoblasts, and adipocytes), and the expression of specific markers (CD105, CD73, and CD90) [ 9 ]. MSCs and their conditioned media (CM) are considered to be promising in regenerative–reparative medicine, cell therapy, and tissue engineering [ 10 , 11 , 12 , 13 , 14 ] due to their effects on tissue and organ homeostasis, revascularization, and tissue repair, as well as their immunomodulatory, anti-inflammatory, pro-angiogenic, pleiotropic, and tropic abilities. For this reason, considerable efforts have been made to introducing advanced MSC-based therapy into clinical practice.…”
mentioning
confidence: 99%